Design and optimization of a new terrain-adaptive hitch mechanism for hilly tractors - Xin, Zhe; Jiang, Qiubo; Zhu, Zhongxiang; Shao, Mingxi (International Journal of Agricultural and Biological Engineering, 2023)
In view of the problems of poor working quality and low efficiency caused by traditional hitch mechanisms, which cannot make farm implements adapt to hillside fields for terrain-adaptive working after leveling the body of hilly tractors, a new type of terrain-adaptive hitch mechanism was designed which can adjust the transverse posture of farm implements to meet the ploughing requirements of complicated terrain in hilly and mountainous areas. The mechanism was mainly composed of the original hitch device and the newly added rotating device. The kinematic model of each sub-mechanism was established, as well as the mathematical relation of significant performance indexes of the whole mechanism, such as lifting capacity, transverse inclination angle and tillage depth. Genetic algorithm was used to optimize the lifting performance of this hitch mechanism in Matlab, so that the minimum vertical lifting force at the center of gravity of farm implements increased by 14.1%, which met the requirements of national standards. Through ADAMS simulation calculation, it was found that different working slopes had a certain influence on the external load of each component, and terrain-adaptive hitch mechanism had little effect on the vibration characteristics of hilly tractors. The fatigue analysis and optimization design of the key component, rotating shaft, were carried out in ANSYS Workbench, and the mass of this part reduced by 64%. A real vehicle test platform was set up to test and verify the power lifting range and working slope range of terrain-adaptive hitch mechanism. The test results showed that the actual power lifting ranged in 185-857 mm, and the maximum error from the theoretical range was only 3.1%, while the actual working slope range was from –25.9° to +23.2°, and the maximum error from the theoretical range was only 4.5%. Therefore, the terrain-adaptive hitch mechanism can meet the requirements of power lifting performance, and simultaneously can adjust the transverse posture of farm implements for adapting to hillside fields of no less than 20°. Keywords: hilly tractors, hitch mechanism, terrain-adaptive working, transverse posture, optimal design DOI: 10.25165/j.ijabe.20231604.6992 Citation: Xin Z, Jiang Q B, Zhu Z X, Shao M X. Design and optimization of a new terrain-adaptive hitch mechanism for hilly tractors. Int J Agric & Biol Eng, 2023; 16(4): 134–144.